The effect of proximity to the northern borders on smoking prevalence among Namibian men - Peter, Tuyenikeumbo Rose (School of Economics, 2016)
This thesis draws on the findings of research in the North America and EU, which shows that price differences of cigarettes between neighboring countries or states (in the Unites States of America) are associated with higher odds of cross border purchase and may lead to smuggling of cigarettes. This results in the tax revenue generation and public health aims of tobacco control policy, through tobacco taxation, being undermined. The Namibian Demographic Health Survey (NDHS) 2013 data is used to assess whether the probability of smoking among Wambo, Lozi and Kwangali Namibian men, living within 150km of the Angolan or Zambian borders, is affected by their proximity to these borders, given that cigarettes are cheaper in Angola and Zambia, than in Namibia. Logistic regressions are used to assess whether proximity to these borders has an effect on the likelihood of smoking, and smoking intensity. The results show that proximity to the border has no statistically significant effect on the probability of smoking or intensity among this group. This may mean that the Namibian government can in fact can pursue more aggressive tobacco taxes, to reduce consumption of tobacco products, without encouraging illicit trade, cross border purchases, or compromising its public health agenda.